2008
DOI: 10.1371/journal.pbio.0060004
|View full text |Cite
|
Sign up to set email alerts
|

Cryptochromes Define a Novel Circadian Clock Mechanism in Monarch Butterflies That May Underlie Sun Compass Navigation

Abstract: The circadian clock plays a vital role in monarch butterfly (Danaus plexippus) migration by providing the timing component of time-compensated sun compass orientation, a process that is important for successful navigation. We therefore evaluated the monarch clockwork by focusing on the functions of a Drosophila-like cryptochrome (cry), designated cry1, and a vertebrate-like cry, designated cry2, that are both expressed in the butterfly and by placing these genes in the context of other relevant clock genes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
321
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(346 citation statements)
references
References 43 publications
24
321
0
1
Order By: Relevance
“…In addition to these core circadian components, Zhu et al (Zhu et al, 2005) discovered that the monarch butterfly, Danaus plexippus, possesses another circadian protein, CRYPTOCHROME2 (CRY2), which is highly homologous to mammalian CRY and is absent in Drosophilia. Yuan et al (Yuan et al, 2007) demonstrated that CRY2 proteins isolated from the monarch butterfly, the malaria mosquito, the honey bee and the flour beetle are light insensitive, and instead repress CLK:CYC-mediated transcription of per in Drosophila Schneider 2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these core circadian components, Zhu et al (Zhu et al, 2005) discovered that the monarch butterfly, Danaus plexippus, possesses another circadian protein, CRYPTOCHROME2 (CRY2), which is highly homologous to mammalian CRY and is absent in Drosophilia. Yuan et al (Yuan et al, 2007) demonstrated that CRY2 proteins isolated from the monarch butterfly, the malaria mosquito, the honey bee and the flour beetle are light insensitive, and instead repress CLK:CYC-mediated transcription of per in Drosophila Schneider 2 cells.…”
Section: Introductionmentioning
confidence: 99%
“…This difference is of interest with regard to the clock system because plant CRYs, such as the ones from Arabidopsis (CRY1 and CRY2), and the animal type I CRYs, such as the one from Drosophila, mediate the input of blue light into clock function (Somers et al, 1998;Stanewsky et al, 1998;Harmer, 2009). On the other hand, animal type II CRYs, represented by mammalian CRYs or monarch butterfly (Danaus plexippus) CRY2, are part of the circadian oscillator (Etchegaray et al, 2003;Zhu et al, 2008). However, not all CRYs are clock-related components.…”
Section: Introductionmentioning
confidence: 99%
“…This implies the diverse roles of magr and cry. Unlike cry, which has already been reported to have other important functions such as circadian rhythm resetting and photosensitivity (Zhu et al, 2008;Chaves et al, 2011), the potential function of magr is to be explored. Since magr is the homologue of bacterial iron-sulfur cluster assembly Isca1, which is evolutionarily highly conserved and found in prokaryotic and eukaryotic organisms for the biogenesis of iron-sulfur cluster across species (Zheng et al, 1998;Schwartz et al, 2001;Vinella et al, 2009), it is predictable that magr may also have similar roles.…”
Section: Discussionmentioning
confidence: 99%